Memórias do Reinado de Nossa Senhora d’ Abadia e do Império do Divino Espírito Santo - Vão de Almas (Cavalcante – GO) - Ribeiro, Joaquim de Sousa (Universidade Federal do Tocantins, 2023)
This research aims to describe the Reign of Nossa Senhora d'Abadia and the Empire of the Divine Espírito Santo, in view of the collective and individual memory of the residents who participate in the event. The methodology took place through observation, analysis and interviews with some participants of this traditional festival. This qualitative approach also included the review of works by authors from the community who dedicated themselves to the study of the topic at hand. We observe that quilombola traditions are essential for strengthening the regional cultural identity, specifically, the Kalunga Historical Site and Cultural Heritage.